2005
DOI: 10.1089/ham.2005.6.60
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hypobaria in Fluid Balance Response to Hypoxia

Abstract: To estimate the separate and combined effects of reduced P(B) and O2 levels on body fluid balance and regulating hormones, measurements were made during reduced PB (altitude, ALT; P(B) = 432 mm Hg, F(I(O2)) = 0.207), reduced inspired O2 concentration (normobaric hypoxia, HYX; P(B) = 614 mm Hg, F(I(O2)) = 0.142), and lowered ambient pressure without hypoxia (normoxic hypobaria HYB; P(B) = 434 mm Hg, F(I(O2)) = 0.296). Nine fit and healthy young men were exposed to these conditions for 10 h in a decompression ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 22 publications
3
65
2
Order By: Relevance
“…However, this is based on the assumption that the response to altitude is solely dependent on O 2 partial pressure and unrelated to barometric pressure. This has been questioned recently (12), and several studies have reported slight differences between the effects of normobaric and hypobaric hypoxia (37,46,54). Most importantly, in the present context, the reduction in CaO 2 seems to be more marked in hypobaric than in equivalent normobaric hypoxia (54).…”
Section: Potential Mechanisms Underlying Lhtlmentioning
confidence: 55%
“…However, this is based on the assumption that the response to altitude is solely dependent on O 2 partial pressure and unrelated to barometric pressure. This has been questioned recently (12), and several studies have reported slight differences between the effects of normobaric and hypobaric hypoxia (37,46,54). Most importantly, in the present context, the reduction in CaO 2 seems to be more marked in hypobaric than in equivalent normobaric hypoxia (54).…”
Section: Potential Mechanisms Underlying Lhtlmentioning
confidence: 55%
“…Change in fluid balance has been reported to be different between HH and NH (18). Compared with HH, NH exposure results in a negative fluid balance, as indicated by a significant decrease in plasma volume.…”
Section: Point: Hypobaric Hypoxia Induces Different Physiological Resmentioning
confidence: 99%
“…Most previous studies have shown that the severity of AMS symptoms were higher in HH than in NH (6,18,20). The potential direct mechanisms (density of breathing gas; N 2 movement or direct influence on CNS) have been discussed (6) but other factors (e.g., hemodynamic factors) require further investigation (18).…”
Section: Point: Hypobaric Hypoxia Induces Different Physiological Resmentioning
confidence: 99%
“…These responses occur within the fi rst hour and persist for 1-2 days. Diuresis and natriuresis occur with subsequent new and greater hypoxic challenges [ 3 ]. Antidiuresis, particularly associated with ADH release, causes the expected urinary concentration.…”
Section: Effects Of Hypoxia On Salt Water and Acid-base Balance Renmentioning
confidence: 99%